Induction of labor in twin gestation: lessons from a population based study. (16th December 2016) - Hamou, Batel; Wainstock, Tamar; Mastrolia, Salvatore Andrea; Beer-Weisel, Ruthy; Staretz-Chacham, Orna; Dukler, Doron; Rafaeli-Yehudai, Tal; Mazor, Moshe; Erez, Offer
Abstract: Introduction: The route of delivery and the role of induction of labor in twin gestations are controversial. The aim of this study was to determine the efficacy of induction of labor in twin gestations. Methods: This retrospective population based cohort study included 4605 twin gestations divided into following groups: 1) spontaneous parturition ( n = 2937, 63.78%); 2) induction of labor ( n = 653, 14.2%) and 3) elective cesarean delivery ( n = 1015, 22.04%). Results: The rate of vaginal delivery in the labor induction group was 81% (529/653). In comparison to the other study groups, induction of labor in twins was independently associated with a 77% reduction in the risk of cesarean delivery (OR 0.23; 95% CI 0.18–0.31) and a 78% reduction in the risk of postpartum death for the second twin (OR 0.22; 95% CI 0.05–0.94). The rate of nulliparity, term delivery and labor dystocia was higher in the induction of labor group ( p < 0.001 in all comparisons). Conclusions: Our results suggest that induction of labor in twin gestation is successful and is independently associated with substantial reduction in the risk of cesarean delivery and postpartum death of the second twin.